Reconfiguring the imperial past: narrative patterns and historical interpretation in Herodian’s History of the empire - Chrysanthu, Chrysanthos S. (Historiography of Rome and its empire, 2022)
In the process of recording the history of the Roman Empire, from the death of Marcus Aurelius to the accession of Gordian III, Herodian makes his characters respond to the same situations in similar or different ways. This book shows that each reign in Herodian’s History is creatively mapped onto ever-recurring narrative patterns. It argues that patterning is not simply decorative in Herodian’s work but constitutes a crucial conceptual and methodological tool for writing interpretative history. Herodian deserves credit as an original and independent author. A careful consideration of the formulaic nature of his historiography indicates that there is more artistry in his composition than had previously been discerned